MOF-integrated Janus cellulose aerogel for solar-driven interfacial desalination with atmospheric water-harvesting capability - Chao Xu; Dan Wang; Ruofei Zhu (Desalination, 2026)

Bioinspired nanocellulose aerogel from spent coffee grounds and natural melanoidins for solar-driven desalination - Dan Wang; Xiaofan Chen; Xueyan Tang; Ruofei Zhu (Desalination, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Application-dependent effects of tea waste biochar on PFAS mobility and N2O and CH4 emissions in agricultural soil - Liting Hao; Dongdong Zhang; Ziheng Zhao; Jun Wang; Ruofei Wang; Miao Li (Waste Management, 2026)

Ultra-stable IrRu-doped NiSe array for highly efficient alkaline overall water electrolysis - Liwen Bie; Qiang Wang; Ruofei Du; Changxiang Shao; Tiansheng Mu; Xiaodong Zhu; Jian Gao (Chemical Engineering Journal, 2026)

Jellyfish-inspired lignin-based MXene hydrogel from waste Apocynum venetum L. stems for solar-driven wastewater treatment - Yunyun Wang; Dan Wang; Ruofei Zhu (Chemical Engineering Journal, 2026)

Orchestrating triacylglycerol biosynthesis and hydrolysis via synthetic genetic circuits enhances spinosad production in Streptomyces albus - Xiaochen Li; Ruofei Guo; Chanjuan Jiang; Ran Liu; Ji Luan; Hailong Wang (Bioresource Technology, 2026)

Alteration of individual morphological brain networks in preschool children with autism spectrum disorder - Weixuan Qin; Chunlan Sun; Shuang Ding; Ruofei Ma; Bin Qin; Kaiping Huang; Yun Zhang; Longlun Wang; Jinhua Cai (Brain Imaging and Behavior, 2026)

A multi-view depth-camera point cloud processing pipeline for pre-harvest maize stand counting - Ruofei Ma; Yuefeng Du; Lei Liu; Dafang Guo; Linze Wang; Du Chen; Zhenghe Song (Biosystems Engineering, 2026)

Low-barrier interface via noble metal induction for external energy-free ppb-level room-temperature formaldehyde sensing - Ziming Yang; Jiangnan Chang; Ying Qiao; Sitao Lv; Leqi Zhang; Yifei Fan; You Wu; Ruofei Lu; Hao Li; Yanan Guo; Patrick J. French; Jun Yin; et al. (Chemical Engineering Journal, 2026)

Catalytic pyrolysis of corn stalks over nitrogen-doped coal gasification fine slag: tar composition refining and phenolic enrichment - Ruofei Wu; Yan Gong; Qinghua Guo; Lu Ding; Guangsuo Yu; Fuchen Wang (Journal of Environmental Management, 2026)

The research of a novelty bio-based flame retardant derived from the synthetic combination of alkaline-extracted polymer substances from wastewater sludge with phytic acid - Congcong Li; Ming Cheng; Ruiqin Chen; Ruofei Wang; Xiangyang Wang; Liang Zhao; Xiaodi Hao; Chen Shi; Wei Zhang (Journal of Environmental Management, 2026)

From firm to soft: Maturity-driven mechanical damage behavior of apples - Zixu Chen; Linlong Jing; Ruofei Liu; Huawei Yang; Linlin Sun; Xinpeng Cao; Yongxian Wang; Shenghui Fu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2026)

Practical or prestige? Technological insights into the production of black-slipped pottery at the Maoershan site in northern Fujian, China - Ruofei Zong; Wenjing Wang; Lin Fu; Wenpeng Xu (Archaeological and Anthropological Sciences, 2026)

Photothermally responsive conductive hydrogels for dual-mode self-sensing soft actuators - Chengnan Qian; Ping Guo; Ruofei Wang; Xuanzi Luo; Yang Yu; Lin Cheng; Aiping Liu (Chemical Engineering Journal, 2025)

Microbial inoculants addition increases microbial necromass but decreases plant lignin contribution to soil organic carbon in rice paddies - Quanyi Hu; Xuelin Zhang; Ziwei Zhang; Ruofei Wang; Cheng Feng; Yingxin Xie; Shaojie Chen; Tianqi Liu (Soil and Tillage Research, 2025)

Revealing the excellent catalytic combustion ability of Cu1.5Mn1.5O4 (222) crystal facet with octahedrally coordinated Mn(Ⅳ)O6 site - Jian Deng; Chunhao Wang; Shenggui Ma; Chengchao Liu; Yongtao Zheng; Haipeng Chen; Ruofei Chen; Siyu Wei; Shanbi Peng; Xia Jiang (Journal of Environmental Chemical Engineering, 2025)

Design, synthesis, bioactivity and action mechanism of N-substituted N′-phenylpicolinohydrazides against phytopathogenic fungi - Yuhao Zhang; Ruofei Bai; Tengyi Du; Yiwei Wang; Bohang Zhou; Congwei Zhou; Le Zhou (Molecular Diversity, 2025)

Tandem catalytic upgrading of cow manure pyrolysis vapors by Beta zeolite and nitrogen-doped activated carbon dual catalysts prepared from coal gasification fine slag to produce light aromatic hydrocarbons - Ruofei Wu; Peng Lv; Xuanxuan He; Yonghui Bai; Jiaofei Wang; Juntao Wei; Weiguang Su; Xudong Song; Guangsuo Yu (Journal of Environmental Chemical Engineering, 2025)

Design, bioactivity and mechanism of N′-phenyl pyridylcarbohydrazides with broad-spectrum antifungal activity - Yuhao Zhang; Bohang Zhou; Pengan Wei; Le Liu; Ruofei Bai; Yiwei Wang; Le Zhou (Molecular Diversity, 2025)

Impact performance of curved double arrow and stacked Miura-ori panels - Zhejian Li; Lingfeng Wang; Ruofei Yan; Yuanpeng He; Hong Hao; Yuanzheng Lin; Wensu Chen (Engineering Structures, 2025)

High dielectric sulfonyl-containing polyimide binders optimize the long-term stability and safety of NCM811 lithium-ion batteries at high voltages - Lin Chen; Dandan Yang; Junhao Xin; Xiaowei Zhou; Yuchen Zhang; Zixin Lv; Tiegen Guo; Qinghai Chen; Ruofei Gao; Ying Wang; Ning Wang; Shuanyan Kang; et al. (Chemical Engineering Journal, 2025)

Online optimization of adjustable settings for agricultural machinery assisted by digital twin - Dafang Guo; Linze Wang; Yuefeng Du; Zhikang Wu; Weiran Zhang; Qiao Zhi; Ruofei Ma (Computers and Electronics in Agriculture, 2024)

LSANNet: A lightweight convolutional neural network for maize leaf disease identification - Fu Zhang; Ruofei Bao; Baoping Yan; Mengyao Wang; Yakun Zhang; Sanling Fu (Biosystems Engineering, 2024)

Predictive modeling of patulin accumulation in apple lesions infected by Penicillium expansum using machine learning - Xiaoyan Cheng; Rongxia Li; Pengdong Xie; Xuexue Wang; Lirong Yu; Ruofei Wu; Huali Xue; Yang Bi (Postharvest Biology and Technology, 2024)

Remediation of arsenic- and nitrate-contaminated groundwater through iron-dependent autotrophic denitrifying culture - Jia-Bo Liu; Hongbin Zhang; Hefei Wang; Banghui He; Huixuan Wang; Ruofei Jin; Tian Tian (Environmental Research, 2024)

Body fluid multiomics in 3PM-guided ischemic stroke management: health risk assessment, targeted protection against health-to-disease transition, and cost-effective personalized approach are envisaged - Ruofei Chen; Xiaoyan Wang; Na Li; Olga Golubnitschaja; Xianquan Zhan (EPMA Journal, 2024)
Because of its rapid progression and frequently poor prognosis, stroke is the third major cause of death in Europe and the first one in China. Many independent studies demonstrated sufficient space for prevention interventions in the primary care of ischemic stroke defined as the most cost-effective protection of vulnerable subpopulations against health-to-disease transition. Although several studies identified molecular patterns specific for IS in body fluids, none of these approaches has yet been incorporated into IS treatment guidelines. The advantages and disadvantages of individual body fluids are thoroughly analyzed throughout the paper. For example, multiomics based on a minimally invasive approach utilizing blood and its components is recommended for real-time monitoring, due to the particularly high level of dynamics of the blood as a body system. On the other hand, tear fluid as a more stable system is recommended for a non-invasive and patient-friendly holistic approach appropriate for health risk assessment and innovative screening programs in cost-effective IS management. This article details aspects essential to promote the practical implementation of highlighted achievements in 3PM-guided IS management.

Eggshell powder as a bio-filler for starch and gelatin: Ternary biodegradable composite films manufactured by extrusion compression molding - Ting Li; Ruofei Li; Haodan Luo; Lu Peng; Jie Wang; Shasha Li; Man Zhou; Xiangyang Yuan; Zhiqing Zhang; Hejun Wu (Food Hydrocolloids, 2024)

Treating reverse osmosis brine of petrochemical wastewater using preparative vertical-flow electrophoresis (PVFE) with multi-objective optimization by response surface method - Rongbo Chen; Tian Tian; Ruofei Jin; Ze Liu; Wang Fu; Qiuyan Ji; Jiti Zhou (Environmental Science and Pollution Research, 2024)

Preparation of ceramsite using solid residue from anaerobic digestion of waste activated sludge and its enhancing effect on catalytic ozonation - Qiang Zheng; Qiuyan Ji; Tian Tian; Ruofei Jin; Ze Liu; Wang Fu; Jiti Zhou (Environmental Research, 2024)

Aromatics production from relay catalytic pyrolysis of cow manure using Ru/C and ZSM-5 dual catalysts synthesized from coal gasification fine slag - Ruofei Wu; Peng Lv; Bin Liu; Yonghui Bai; Jiaofei Wang; Juntao Wei; Weiguang Su; Guangyu Xu; Weina Bao; Guangsuo Yu (Journal of Environmental Management, 2023)

Plasticizer phthalate esters degradation with a laccase from Trametes versicolor: effects of TEMPO used as a mediator and estrogenic activity removal - Dan Wang; Ruofei Zhu; Jiangfei Lou; Nawon Baek; Xuerong Fan (Biodegradation, 2023)

Biomimetic optimized concept with Murray networks for accelerated solar-driven water evaporation - Ruofei Zhu; Ke Li; Dan Wang; Jipeng Fei; Jun Yan Tan; Shuzhou Li; Jichao Zhang; Hong Li; Shaohai Fu (Chemical Engineering Journal, 2023)

Catalytic upgrading of cow manure pyrolysis vapors over zeolite/carbon composites prepared from coal gasification fine slag: High quality bio-oil obtaining and mechanism investigation - Ruofei Wu; Peng Lv; Jiaofei Wang; Yonghui Bai; Juntao Wei; Xudong Song; Weiguang Su; Guangsuo Yu (Fuel, 2023)

Research on Coal Pillar Width and Support Design of Gob-Side Entry - Yong Yang; Jian Sun; Wei Wang; Ruofei Zhang (Geotechnical and Geological Engineering, 2023)

Facile preparation of coprecipitates between iron oxides and dissolved organic matter for efficient Fenton-like degradation of norfloxacin - Huali Yu; Guangfei Liu; Lingyu Shen; Ruofei Jin; Jiti Zhou; Haiyan Guo; Lianfeng Wang (Journal of Hazardous Materials, 2023)

Fabrication of Nanosuspensions to Improve the Oral Bioavailability of Total Flavones from Hippophae rhamnoides L. and their Comparison with an Inclusion Complex - Rui Tian; Hui Wang; Yi Xiao; Pengyue Hu; Ruofei Du; Xiufeng Shi; Zhengtao Wang; Yan Xie (AAPS PharmSciTech, 2020)

Enhanced bioreduction of nitrobenzene by reduced graphene oxide materials: effects of surface modification and coexisting soluble electron shuttles - Guangfei Liu; Bin Dong; Jiti Zhou; Jing Wang; Ruofei Jin; Juanjuan Li (Environmental Science and Pollution Research, 2017)

Microbial synthesis of bimetallic PdPt nanoparticles for catalytic reduction of 4-nitrophenol - Ya Tuo; Guangfei Liu; Bin Dong; Huali Yu; Jiti Zhou; Jing Wang; Ruofei Jin (Environmental Science and Pollution Research, 2017)

National serosurvey of encephalomyocarditis virus in healthy people and pigs in China - Ruofei Feng; Jia Wei; Haixia Zhang; Jingjing Fan; Xiangrong Li; Dan Wang; Jingying Xie; Zilin Qiao; Mingsheng Li; Jialin Bai; Zhongren Ma (Archives of Virology, 2015)

Accelerated removal of Sudan dye by Shewanella oneidensis MR-1 in the presence of quinones and humic acids - Guangfei Liu; Jiti Zhou; Qiuyan Ji; Jing Wang; Ruofei Jin; Hong Lv (World Journal of Microbiology and Biotechnology, 2013)

Site-directed mutagenesis of substrate binding sites of azoreductase from Rhodobacter sphaeroides - Guangfei Liu; Jiti Zhou; Jing Wang; Bin Yan; Jingmei Li; Hong Lu; Yuanyuan Qu; Ruofei Jin (Biotechnology Letters, 2008)